Cardiorespiratory Fitness and Neuromuscular Function of Mechanically Ventilated ICU COVID-19 Patients*. Issue 11 (14th September 2022) - Millet, Guillaume Y.; Kennouche, Djahid; Foschia, Clément; Brownstein, Callum G.; Gondin, Julien; Lapole, Thomas; Rimaud, Diana; Royer, Nicolas; Thiery, Guillaume; Gauthier, Vincent; Oujamaa, Lydia; Sorg, Marine; et al.
Abstract : OBJECTIVES: The aim of the current study was to investigate the level of cardiorespiratory fitness and neuromuscular function of ICU survivors after COVID-19 and to examine whether these outcomes are related to ICU stay/mechanical ventilation duration. DESIGN: Prospective nonrandomized study. SETTING: Patients hospitalized in ICU for COVID-19 infection. PATIENTS: Sixty patients hospitalized in ICU (mean duration: 31.9 ± 18.2 d) were recruited 4–8 weeks post discharge from ICU. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Patients visited the laboratory on two separate occasions. The first visit was dedicated to quality of life questionnaire, cardiopulmonary exercise testing, whereas measurements of the knee extensors neuromuscular function were performed in the second visit. Maximal oxygen uptake (Vo 2 max) was 18.3 ± 4.5 mL·min –1 ·kg -1, representing 49% ± 12% of predicted value, and was significantly correlated with ICU stay/mechanical ventilation (MV) duration ( R = –0.337 to –0.446; p < 0.01 to 0.001), as were maximal voluntary contraction and electrically evoked peak twitch. Vo 2 max (either predicted or in mL· min –1 ·kg -1 ) was also significantly correlated with key indices of pulmonary function such as predicted forced vital capacity or predicted forced expiratory volume in 1 second ( R = 0.430–0.465; p ≤ 0.001) and neuromuscular function. Both cardiorespiratory fitness and neuromuscular function were correlated with self-reported physical functioning and general health status. CONCLUSIONS: Vo 2 max was on average only slightly above the 18 mL·min –1 ·kg -1, that is, the cut-off value known to induce difficulty in performing daily tasks. Overall, although low physical capacities at admission in ICU COVID-19 patients cannot be ruled out to explain the association between Vo 2 max or neuromuscular function and ICU stay/MV duration, altered cardiorespiratory fitness and neuromuscular function observed in the present study may not be specific to COVID-19 disease but seem applicable to all ICU/MV patients of similar duration.